An Analysis of the Criminal Liability of Medical Personnel in Illegal Abortion Cases in Indonesia - Sudarmanto Sudarmanto; Sri Endah Wahyuningsih (UNISSULA Semarang, 2025)
Abstract. The Preamble of the 1945 Constitution affirms the state’s objectives to protect all citizens, promote welfare, enlighten the nation, and uphold justice. Law as the state’s pillar guarantees order and protection of individual rights, including the fetus’s right to life. The phenomenon of illegal abortion arises from social pressures, unplanned pregnancies, and lack of education. Law enforcement and protection of women’s reproductive rights are crucial to prevent illegal abortion while maintaining justice and social welfare. The research aims to describe and analyze criminal liability of medical personnel in illegal abortion cases in Indonesia and to describe and analyze legal principles relevant to determining their liability under criminal law doctrine. This research applies a qualitative legal method with a normative juridical approach and descriptive character. Secondary data are obtained from primary, secondary, and tertiary legal materials through literature study. Qualitative descriptive analysis is employed to examine criminal liability of medical personnel in illegal abortion cases in Indonesia systematically and comprehensively. The research results show that criminal liability of medical personnel in illegal abortion cases in Indonesia is strictly regulated in the Criminal Code Articles 346 to 349, and Law No. 17 of 2023 on Health prohibits abortion, except as stipulated in the Criminal Code. Articles 427–428 of the Health Law impose imprisonment up to 15 years, with aggravation for medical personnel and potential revocation of practice licenses. Government Regulation No. 28 of 2024 as implementing regulation allows safe abortion in cases of pregnancy due to sexual violence, medical emergencies, and pregnancies up to 14 weeks under the new Criminal Code. Comparisons with other countries, such as Singapore allowing abortion up to 24 weeks with mandatory counseling and Cambodia permitting abortion up to 12 weeks for any reason, show Indonesia’s stricter regulation. Based on MUI Fatwa No. 4 of 2005, abortion for rape victims is permissible before the fetus reaches 40 days due to emergency grounds. The Indonesian Medical Code of Ethics emphasizes that illegal abortion constitutes both ethical and legal violations, underlining the principles of non-maleficence, protection of life, and the purpose of law enforcement to deter and prevent unsafe abortion practices. The relevant legal principles in determining criminal liability of medical personnel performing illegal abortions under criminal law doctrine are that criminal law principles serve as essential guidelines, including the principle of legality, principle of fault, principle of no crime without act, principle of proportionality, and principle of protection of legal interests. The principle of legality ensures punishment only when stipulated by law, the principle of fault requires intent or negligence, and the principle of no crime without act demands proof of actual conduct. The proportionality principle guarantees balance between punishment and culpability, while the principle of protection of legal interests safeguards the fetus’s right to life, maternal health, public order, and the integrity of the medical profession.